2020
DOI: 10.1097/scs.0000000000006305
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Maxillary Position Using a Computer-Aided Design/Computer-Aided Manufacturing Intermediate Splint Derived Via Surgical Simulation in Bimaxillary Orthognathic Surgery

Abstract: Purpose: The purpose of this study was to assess the clinical interventions and the accuracy of maxillary reposition using a computer-aided design/computer-aided manufacturing (CAD/CAM) splint derived via surgical simulation. Materials and Methods: The retrospective study comprised 24 patients who underwent bimaxillary surgery. The patients were assigned to 1 of 2 groups by a way of maxillary repositioning. One group received conventional intermediate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…32 Recent advances in 3D computer-aided design/computeraided manufacturing technology has enabled clinicians to fabricate surgical wafers and simulate surgical movements 33 as well as the validation of maxilla stability after orthognathic surgery. 34 Simulation surgery and 3D computer-aided design/computer-aided manufacturing splints 35 and condyle positioning jigs 15 have been developed for such stabilization during orthognathic surgery. Lee et al, 22 developed a type of computer-assisted surgery protocol for managing the proximal segment while treating complex maxilla-facial deformities.…”
Section: Discussionmentioning
confidence: 99%
“…32 Recent advances in 3D computer-aided design/computeraided manufacturing technology has enabled clinicians to fabricate surgical wafers and simulate surgical movements 33 as well as the validation of maxilla stability after orthognathic surgery. 34 Simulation surgery and 3D computer-aided design/computer-aided manufacturing splints 35 and condyle positioning jigs 15 have been developed for such stabilization during orthognathic surgery. Lee et al, 22 developed a type of computer-assisted surgery protocol for managing the proximal segment while treating complex maxilla-facial deformities.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have used voxel-based matching to superimpose the preoperative and postoperative cone beam computed tomography (CBCT) scans for assessing surgical accuracy and for identifying factors that may influence or affect the feasibility of 3D VSP [ 4 , 5 ]. Recent studies reported that the accuracy of maxillary positioning in non-cleft patients using a computer-aided design/computer-aided manufacturing (CAD/CAM) splint derived from 3D VSP is within the range of 1 to 2 mm [ 6 , 7 ]. Studies with similar study design involving cleft patients demonstrated that the surgical accuracy of maxillary positioning varied between 1.48 and 2.75 mm [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…3 In this way, a more precise surgical method than the conventional one is achieved. 4 Despite the precision with which skeletal surgeries are performed today, the evidence regarding the reaction of soft tissues to the skeletal movement of orthognathic or orthofacial surgery varies widely. [5][6][7][8] Conversely, the literature shows limited information about the relationship between hard and soft tissues in the 3D analysis, rendering the process at the soft tissue level unpredictable.…”
mentioning
confidence: 99%
“…This flow includes: (1) image acquisition of bone hard tissues with cone beam computed tomography (CBCT), (2) image acquisition of dental hard tissues and occlusion with an intraoral scanner, (3) reconstruction of soft tissues using 3D photographs, (4) video of functional movements, (5) image superimposition, (6) virtual planning and treatment, and (7) design and printing of surgical and cutting guides 3 . In this way, a more precise surgical method than the conventional one is achieved 4 …”
mentioning
confidence: 99%